The complete chloroplast genome of Allium wallichii Kunth (Amaryllidaceae) - Jin Zhao; Miao Huang; Rui Ni; Ting Peng; Xiaoyulong Chen; Hong Nan (Mitochondrial DNA. Part B. Resources, 2023)
Allium wallichii Kunth is a herb species with potentially extensive applications because of its edible, ornamental, and pharmaceutical values. The structural characteristics and phylogenetic relationships of its chloroplast genome were determined here for the first time. The complete cp genome was found to be 152,496 bp long, with a GC content of 37.04%. It consists of four distinct regions: a large single copy (LSC) region of 82,510 bp, a small single copy (SSC) region of 17,460 bp, and two inverted repeat (IR) regions of 26,263 bp each. The genome encodes 129 genes, including 86 protein-coding genes, 37 tRNA genes, and six rRNA genes. Our phylogenetic analysis revealed that A. wallichii was closely related to Allium wallichii var. platyphyllum, which are included in the section Bromatorrhiza, subgenus Amerallium Traub of the genus Allium. Our report provides valuable information on the genetic diversity of Allium species.